Record of the storage mite Tyrophagus longior (Gervais)(Acari: Astigmata: Acaridae) in southern Syria (Damascus University Journal of agriculture sciences, 2024)
This study was carried out during 2022–2023 at the Department of Plant Protection laboratories (Faculty of Agriculture, University of Damascus). Two populations of Tyrophagus longior (Gervais( (Acari: Acaridae) were herein reported. All stages of T. longior were observed on (i)Morusnigra leaves (Moraceae) at the Faculty of Agriculture Campus, and (ii) in the in vitro cultures of Botrytis cinerea (Sclerotiniaceae)feeding on both spores and mycelium at the Scientific Agricultural Researches Center (As-Suwayda Governorate).This Astigmatid mite is a cosmopolitan member of the family Acaridae, reported from a large variety of habitats such as stored foods, greenhouse plants, several crops, and bumblebee,mice and birds' nests. It has been also reported infesting fungiculture mediums and insect diets in laboratory. This is the first record of this pest of southern Syria, which adds a new host association and widens the mite fauna in Syria.
Keywords: Mite; Tyrophagus Longior; Acaridae; Astigmata; Syria